An Inquiry-Based Environmental Physics Module for Scientific Literacy: Development and Validation - Jannah, Misbahul; Mazlina, Hilda; Oviana, Wati; Lailatussaadah, Lailatussaadah; Mustika, Cut Riziki; Halim, Lilia (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Scientific literacy is a fundamental competency for prospective physics teachers, yet inquiry-oriented instructional materials specifically designed for environmental physics remain limited. This study developed and validated an inquiry-based environmental physics module intended to strengthen scientific literacy in physics teacher education. A research and development approach based on the Dick and Carey instructional design model was employed, encompassing needs analysis, instructional design, module development, expert validation, revision, and limited user evaluation. The module was reviewed by experts in instructional materials and physics education, followed by a practicality evaluation involving prospective physics teachers enrolled in an Environmental Physics course. Data were collected using structured validation instruments and user feedback questionnaires, with qualitative comments informing iterative revisions. The findings indicate that the developed module achieved high levels of content validity and practical feasibility. Expert recommendations contributed to improvements in visual presentation, learning content, student worksheets, instructional planning, and scientific literacy assessment components. The finalized module integrates environmental physics concepts with structured inquiry activities that encourage scientific reasoning, evidence-based investigation, and contextual problem solving. These findings demonstrate that the module provides a valid and practical instructional resource for supporting scientific literacy among prospective physics teachers and offers a useful reference for developing inquiry-oriented instructional materials in physics teacher education.